The Russian Economy: Searching for Effective Strategy - Elena B. Lenchuk; Vladimir I. Filatov (Мир новой экономики)
Subject. The subject of the article is an analysis of approaches to the definition of a long-term strategy for the development of the Russian economy in the context of the transition to a new model of economic growth that will ensure a stable and dynamic development of the national economy. Goals. The authors set themselves the following main tasks: the first is to define targets for improving the economic dynamics of the Russian economy based on the assessment of the current situation in the Russian economy. The second is to study the proposals and recommendations of the leading institutions and centers for bringing the economy to the trajectory of sustainable growth. The third is to supplement and clarify these proposals and recommendations with their own proposals. Methods. The analysis of the materials of the Center for Strategic Research (headed by A. Kudrin) and the “Growth Strategies” program (headed by B. Titov) made it possible to identify those proposals and recommendations that can be used to prepare the country’s long-term economic growth program. Results. The article suggests structural priorities for economic growth and specifies the features of accelerated technological modernization of industrial potential and large-scale development of the country’s infrastructure, which can significantly complement and expand the recommendations and proposals of leading economic centers and, at the end, significantly accelerate the solution of the country’s economic and social problems.